Solid Polymer-in-Ceramic Electrolyte Formed by Electrophoretic Deposition. Issue 11 (1st January 2015) - Blanga, R.; Burstein, L.; Berman, M.; Greenbaum, S. G.; Golodnitsky, D.
Abstract : We present here a new solid composite polymer-in-ceramic electrolyte formed by electrophoretic deposition (EPD) and saturated with lithium iodide. Composite films have been characterized by ESEM, MTGA, XPS, NMR and impedance-spectroscopy methods. We have found that the EPD of polyethylene oxide alone is impossible, either from acetone- or from ethanol-based suspensions. Addition of polyethylene imine to the suspension increases the deposition rate of both LiAlO2 ceramic particles and polyethylene oxide, and the duration of stirring increases the PEO content in the film. Composite LiAlO2 :LiI:P(EO)3+x electrolyte, in which salt/ceramic grain-boundaries play a dominant role in lithium-ion transport, is characterized by high, temperature-independent conductivity (0.5 mS/cm). Lithium-ion species of higher and lower mobility have been distinguished in NMR spectra. Deconvolution of the spectra revealed that the fraction of the more mobile lithium ions was about 2% between 25 and 65°C, and it increases to 10% above 70°C.